The effects of a mindfulness-based lifestyle programme for adults with Parkinson's disease: protocol for a mixed methods, randomised two-group control study. Issue 10 (10th October 2013) - Advocat, Jenny; Russell, Grant; Enticott, Joanne; Hassed, Craig; Hester, Jennifer; Vandenberg, Brooke
Abstract : Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disorder in developed countries. There is an increasing interest in the use of mindfulness-related interventions in the management of patients with a chronic disease. In addition, interventions that promote personal control, stress-management and other lifestyle factors, such as diet and exercise, assist in reducing disability and improving quality of life in people with chronic illnesses. There has been little research in this area for people with PD. Methods: A prospective mixed-method randomised clinical trial involving community living adults with PD aged <76 years and with moderate disease severity (Hoehn and Yahr stage 2) PD. Participants will be randomised into the ESSENCE 6-week programme or a matched wait list control group. ESSENCE is a multifaceted, healthy lifestyle and mindfulness programme designed to improve quality of life. We aim to determine whether participation in a mindfulness and lifestyle programme could improve PD-related function and explore self-management related experiences and changing attitudes towards self-management. The outcome measures will include 5 self-administered questionnaires: PD function and well-being questionnaire (PDQ39), Health Behaviours, Mental health, Multidimensional locus of control, and Freiburg mindfulness inventory. An embedded qualitative protocol will include in-depth interviews with 12 participants before and after participation in the 6-week programme and a researcher will observe the programme and take notes. Analysis: Repeated measures of Analysis of Variance (ANOVA) will examine the outcome measures for any significant effects from the group allocation, age, sex, adherence score and attendance. Qualitative data will be analysed thematically. We will outline the benefits of, and barriers to, the uptake of the intervention. Ethics: This protocol has received ethics approval from the Monash University Human Research Ethics Committee project number CF11/2662–2011001553. Dissemination: This is the first research of its kind in Australia involving a comprehensive, lifestyle-based programme for people with PD and has the potential to involve a broader range of providers than standard care. The findings will be disseminated through peer reviewed journals, primary care conferences in Australia as well as abroad and through the Parkinson's community. Registration details: Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12612000440820.